Safety of nab-paclitaxel following an allergic reaction to paclitaxel: A single institution retrospective study - Swapna Kochuveettil; Roberto Angeli Morales; Alicja Kaminska; Gerardo Colon-Otero (Elsevier, 2024)
The goal of this study was to assess the safety of nab-paclitaxel in patients with ovarian cancer or endometrial cancer who had an allergic reaction to paclitaxel. We performed a retrospective review of patients with endometrial cancer or ovarian cancer with an allergic reaction to paclitaxel who were subsequently treated with nab-paclitaxel at the Mayo Clinic Florida from January 2016 to June 2023. A total of 43 patients with ovarian cancer (31) or endometrial cancer (12) and a paclitaxel allergic reaction were identified. All patients were pre-medicated against allergic reactions prior to paclitaxel and subsequent nab-paclitaxel. Allergic reactions to paclitaxel were mild in fourteen patients (33%), moderate in twenty-five patients (58%) and severe in four (9%) patients. None of the 43 patients had an allergic reaction to subsequent nab-paclitaxel. Our data suggests that the administration of nab-paclitaxel to endometrial cancer or ovarian cancer patients with allergic reactions to paclitaxel is safe and should be considered a preferable treatment option in this clinical situation.